Theory of Algorithmic Self-Assembly. - Doty, David (Communications of the ACM, 2012)
The article explores algorithmic self-assembly, or systems that can automate a series of growth tasks related to the machine's own growth. It focuses on the application of this theory to nanoscience and automating the growth of molecular structures, as the author notes that nanoscience justifies the study of computation. Information is provided on molecular computing, research into DNA (deoxyribonucleic acid), and the abstract Tile Assembly Model (aTAM), combinatorial model of the dynamic behavior of DNA tiles.